2014
DOI: 10.1021/ic500563j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chemical Synthesis and Characterization of CeTi2O6 Brannerite

Abstract: Cerium titanate CeTi2O6 was prepared by a new soft chemistry route in aqueous solution. A suite of characterization techniques, including X-ray diffraction, thermal analysis, vibrational spectroscopy, and scanning and transmission electron spectroscopy, were employed to investigate the brannerite structure formation and its bulk properties. The synthesized powder formed the brannerite crystal structure upon calcination at temperatures as low as 800 °C. Samples sintered at 1350 °C possess a high level of crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 34 publications
7
32
0
Order By: Relevance
“…The pelletized precursors U1 and U2 were then sintered in air at 1200/1300°C to produce samples U1B/U1C and U2B/U2C, respectively. The XRD patterns of samples U1B (Figure A) and U2B (Figure B) showed typical brannerite in good agreement with the XRD patterns of CeTi 2 O 6 and UTi 2 O 6 (JCPDS card No. 00‐012‐0477) in monoclinic C 2/ m space group.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The pelletized precursors U1 and U2 were then sintered in air at 1200/1300°C to produce samples U1B/U1C and U2B/U2C, respectively. The XRD patterns of samples U1B (Figure A) and U2B (Figure B) showed typical brannerite in good agreement with the XRD patterns of CeTi 2 O 6 and UTi 2 O 6 (JCPDS card No. 00‐012‐0477) in monoclinic C 2/ m space group.…”
Section: Resultsmentioning
confidence: 98%
“…The refined unit cell parameters are summarized in Table , together with those of CeTi 2 O 6 and some substituted UTi 2 O 6 and ThTi 2 O 6 brannerite phases available in the literature. The unit cell volume ( V ), the b ‐parameter and c ‐parameter show good linear relationships with the Shannon ionic radii of the A‐site cations in ATi 2 O 6 , while the a ‐parameter shows weak relationship with the ionic radii of the A‐site cations (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…00‐025‐0177) with trace amounts of UO 2 . The refined unit cell parameters for sample U1 (as same composition to sample U2) are summarized in Table , together with those for Ce 0.975 Ti 2 O 5.95 , UTi 2 O 6 , Y 0.15 Th 0.6 Pu 0.25 Ti 2 O 5.925 , and Y 0.15 Th 0.6 Np 0.25 Ti 2 O 5.925 for comparison. The refinement of sample U1 gives reasonably well R factor, 7.88 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work demonstrated that end‐member CeTi 2 O 6 , ThTi 2 O 6 , and UTi 2 O 6 brannerite phases could be stabilized by high temperature (1200°C‐1400°C) sintering. However, brannerite phase crystallization in glass remains little studied.…”
Section: Methodsmentioning
confidence: 99%
“…The TiO 6 layers are connected along the c axis by corner-sharing with CeO 6 octahedra 41,42. CeTi 2 O 6 as well as anatase and rutile polymorphs of TiO 2 were observed as…”
mentioning
confidence: 99%